THE COMPOSITION OF ENGINEERING AND GEODETIC SURVEYS OF LINEAR STRUCTURES - Tashpulatov Sarvar Anvarovich; Kadyrov Askar Anvarovich (Galaxy International Interdisciplinary Research Journal, 2021)
In the production of engineering and geodetic surveys of linear structures, the geodetic basis is the points (points) of a planned high-altitude survey geodetic network created in the form of main passages laid along the route.The article discusses the composition of engineering and geodetic surveys of linear structures and general requirements for them.